Raman spectroscopy as a tool for magnesium estimation in Mg‐calcite - Borromeo, Laura; Zimmermann, Udo; Andò, Sergio; Coletti, Giovanni; Bersani, Danilo; Basso, Daniela; Gentile, Paolo; Schulz, Bernhard; Garzanti, Eduardo (Journal of Raman spectroscopy, 2017)
Despite their strong Raman scattering and importance in several applications in the geological and biological sciences, Mg‐calcites have not been thoroughly investigated by Raman spectroscopy. In this study, we investigated whether Raman spectra of carbonates are sensitive to the structural and chemical changes occurring when Mg2+ substitutes Ca2+ in the calcite lattice. Different carbonate samples with variable Mg content (from 0 to 20 mol% MgCO3) of biological and inorganic origin have been first beamed under a Raman spectrometer and then analysed by scanning electron microscopy‐energy dispersive spectrometer and electron microprobe analysis‐wavelength dispersive spectrometer microprobes to determine their chemistry. The biological samples (foraminifers, algae, barnacles and echinoderms) were collected from areas situated at different latitudes and water temperature and saturation, factors affecting the chemical and isotopic composition of shells in marine organisms. The Raman band positions are directly linked to the amount of magnesium present in the calcite lattice, and all peaks of Mg‐calcite spectra show a consistent and linear increase in Raman shifts according to their Mg content, which is a consequence of the decreased inter‐atomic distances following the substitution of Ca2+ with the smaller Mg2+ ion. This study demonstrates that Raman spectroscopy provides an innovative work perspective in marine biology, provenance studies and oil exploration when estimates of mineralogical and chemical changes are the focus of the study. Raman spectroscopy is even more attractive – for the mentioned fields of research – than many other methods because of the non‐destructive nature and its very short analytical time. Copyright © 2017 John Wiley & Sons, Ltd. Different biological calcite samples with variable Mg content have been first beamed under a Raman spectrometer and then analysed by electron microprobes to determine their chemistry. The band positions are linked to the amount of magnesium present, and all peaks of Mg‐calcite spectra show a linear increase in Raman shifts according to their Mg content. Two graphs and three equations to estimate Mg content from the peaks positions have been provided.